2011
DOI: 10.4238/vol10-3gmr1107
|View full text |Cite
|
Sign up to set email alerts
|

RAPD and ISSR markers in the evaluation of genetic divergence among accessions of elephant grass

Abstract: ABSTRACT. Considering the expected genetic variability of elephant grass (Pennisetum purpureum), due to its cultivation in different continents, we characterized and estimated the genetic divergences between 46 accessions of elephant grass with different edaphoclimatic adaptations, using RAPD and ISSR markers. We evaluated, comparatively, the consistency of the information achieved with these markers. Twenty-six RAPD and 25 ISSR primers were employed. The RAPD markers produced 185 bands, 72% of which were poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 31 publications
1
32
0
2
Order By: Relevance
“…Interestingly, these results also did not reveal the clustering of different accessions according to their geographical origin, which was demonstrated by the previous morphological, agronomic and RAPD marker studies. Other types of molecular markers, such as inter-sequential simple repeat (ISSR) markers [41,45] and sequence-related amplified polymorphisms (SRAPs) [46] have also been used for the characterization and identification of Napier grass clones.…”
Section: Genetic Resources Molecular Diversity and Breedingmentioning
confidence: 99%
“…Interestingly, these results also did not reveal the clustering of different accessions according to their geographical origin, which was demonstrated by the previous morphological, agronomic and RAPD marker studies. Other types of molecular markers, such as inter-sequential simple repeat (ISSR) markers [41,45] and sequence-related amplified polymorphisms (SRAPs) [46] have also been used for the characterization and identification of Napier grass clones.…”
Section: Genetic Resources Molecular Diversity and Breedingmentioning
confidence: 99%
“…The female parents were selected based on late flowering, high DM yield, stem diameter (Rossi, 2010), and genetic divergence in relation to male parents, in accordance with Lima et al (2011). Male parents were selected based on the genetic divergence in relation to the female parents, and genetic divergence in relation to female parents (Lima et al, 2011), and also based on their morpho-agronomic traits (DM yield, stem diameter, number of tillers) (Rossi, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Male parents were selected based on the genetic divergence in relation to the female parents, and genetic divergence in relation to female parents (Lima et al, 2011), and also based on their morpho-agronomic traits (DM yield, stem diameter, number of tillers) (Rossi, 2010). Among these genotypes, ten parents were chosen, five females (P1, P2, P3, P4, and P5) (group I) and five males (P6, P7, P8, P9, and P10) (group II), forming a 5 × 5 partial diallel (Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that different markers might reveal different kinds of variation (Powell et al, 1996). RAPD markers (Williams et al, 1990) and ISSR markers (Zietkiewicz et al, 1994) have been used with success to identify and determine relationships at the species, population, and cultivar levels in many plant species, including several aromatic and medicinal plants (Mattioni et al, 2002;Nan et al, 2003;Fracaro et al, 2005;Manica-Cattani et al, 2009;de Lima et al, 2011). However, there are limited reports on the genetic relationships of Achillea species.…”
Section: Introductionmentioning
confidence: 99%